Strandings of Longman’s beaked whale (Indopacetus pacificus) in the Philippines - Acebes, Jo Marie; Yamada, Tadasu; Poniente, Jennifer; Matsuda, Ayaka; Dolar, Ma. Louella; Espiritu, Marco; Tan, Jose Ma. Lorenzo; Tan, Jose Ma. Lorenzo; Santos, Mudjekeewis (J. Cetacean Res. Manage., 2022)
Longman’s beaked whale, Indopacetus pacificus, is one of the least known of all cetacean species. Its external appearance was only first described in the 21st century. Prior to 2004, the species was known from only six specimens. Although at least twenty more specimens were recovered from strandings since then, knowledge on the species is still very limited. In the Philippines, the first record of the species was confirmed through a stranding in Davao in 2004. Sightings of Indopacetus pacificus alive at sea in the Philippines remain unconfirmed. Herein we account for all the strandings of the species in the Philippines and describe the specimens collected and their status based on examined stranding reports and actual examination of the specimens conducted by one or more co-authors. To date, there are four confirmed strandings of the species, all sub-adult individuals, which occurred at four different sites: 1.) 5.73m male at Matina-Aplaya, Davao in 2004; 2.) 5.02m male at General Nakar, Quezon in 2016; 3.) 5.4m male at Gonzaga and 4.) 5.6m male at Sta. Ana, both in Cagayan Province in 2018. Three of the strandings occurred at northern Luzon, while one in southern Mindanao. Two out of four stranded alive but died shortly after. From three of these the skeleton, stomach contents and tissue samples were examined and collected. Squid beaks, squid eye lenses and fish eye lenses were found in the stomach. DNA analysis using mitochondrial CytB and COI sequences showed that the three (3) specimens were indeed I. pacificus. The skeletal specimen collected from Sta. Ana, Cagayan is by far the most complete in the country and is probably in one of the best conditions in the world. For a cetacean species that is poorly known examination of stranded specimens offers a rare opportunity to collect information. Hence, the importance of standardizing necropsy and stranding data collection protocols, training stranding first-responders and establishing a database are emphasized.